The Fears of Losing the National Identity and the Ways of Counteracting Them - Zakaryan, Seyran (Bulletin of Yerevan University E: Philosophy, Psychology, 2022)
The following idea is put forward in the article that for a long time among the Armenians the stress was mainly laid not on the modernization and enrichment of national identity but mainly on its protection for different reasons especially because of being deprived of the state and invariability of unfavourable conditions. At the core of this position lay the fears of losing identical elements, the active ways of counteraction of which are the armed struggle and freedom fight, and the passive ways are traditionalism, secrecy, separation-isolation and removal. The article discusses the passive ways of counteraction at the core of which lays the position that the supporting columns of the national identity, i.e. homeland, nation, religion and faith, language, culture, historical past, etc., and what was bequeathed us should not be refused in any case and in any condition. The passive ways were reliable mechanisms of protecting the national identity especially in the Middle Ages , when the traditional way of thinking was prevailing and nationality was identical to the religion and faith. But for a long time the strategy of keeping the identity only due to those things had (and has) its negative effects besides positive ones (for example, in the Middle Ages they were manifested in religious struggles). First of all traditionalism, especially its radical wing, denies innovations thus preventing the modernization and modification of identical paradigm. Secondly, the position of isolation supposes a change of the way of thinking and acting, a program of principles and bases of its own life organization, i. e. the political vision of becoming powerful, the system of national education, protection and development of national values. Though separating themselves from the outer world, the Armenians mostly were led by the philosophy of traditional existence and did not develop a biophilosophy and ideology of the separated. And the proved way of developing and becoming powerful and acting according to the spirit of time is the sensible and original combination of the traditional and the modern, the native and the alien, the construction of a new layer of civilization based on the tradition.
Keywords: national identity; fear; conservatism; traditionalism; secrecy; self-isolation; historical memory; the identity in the Medieval Ages; the policy of identity